الخواص الميكانيكية للبيتون المصنع باستخدام حصويات بيتونية معاد تدويرها مأخوذة من منطقة سلمى - بسـام حويجـة; نزيه منصور; أحمد ناصر (Tishreen University, 2019)
The increasing urbanization of the world and the demands of new buildings in line with growing population growth are creating a major problem in securing the raw materials needed for the construction of these new buildings, especially the bulk of these materials. This means paying attention to finding a way or ways to reduce the depletion of raw materials for the concrete industry, most importantly recycling. Many countries have succeeded in utilizing waste in general and construction waste in particular by recycling waste and producing building materials that play the same role as conventional building materials in providing natural resources exploitation and achieving sustainability for future generations. The main objective of the research is to study the replacement of the natural aggregates used in the concrete with recycled concrete aggregates properties resulting from the state of destruction in the Salma area according to the replacement ratios of 0%, 25%, 50%, 75%, 100%, and the effect on the behavior of the concrete compared to the concrete With natural aggregates, with a better replacement ratio. The results showed a decrease in the resistance of the concrete to pressure, tensile strength, flexural Strength and low volumetric weight as well, by increasing the ratio of replacement natural aggregates with recycled concrete aggregates. إن التوسع العمراني المتزايد في العالم ومتتطلبات الأبنية الجديدة المتوافقة مع تزايد النمو السكاني يولد مشكلة كبيرة تتعلق بتأمين المواد الأولية اللازمة لتشييد هذه الأبنية الجديدة, وخصوصاً الحصويات التي تشكل الحجم الأكبر من هذه المواد. هذا يعني توجيه الاهتمام إلى ايجاد طريقة أو طرق للحد من استنزاف المواد الأولية لصناعة البيتون، وأهمها إعادة تدويره. وقد نجحت العديد من الدول في الاستفادة من المخلفات بصفة عامة ومخلفات البناء بصفة خاصة عن طريق إعادة تدوير تلك المخلفات, وإنتاج مواد بناء تقوم بنفس الدور الذي تقوم به مواد البناء التقليدية وذلك للحد من استغلال الموارد الطبيعية وتحقيق مبدأ الاستدامة للأجيال القادمة. إن الهدف الرئيسي للبحث هو دراسة استبدال الحصويات الطبيعية المستخدمة في البيتون بحصويات بيتونية معاد تدويرها ناتجة عن حالة الدمار في منطقة سلمى وذلك وفق نسب استبدال 0%، 25%، 50%، 75%، 100%، وتأثير ذلك على سلوك البيتون مقارنة مع البيتون ذو الحصويات الطبيعية، مع تحديد نسبة الاستبدال الفضلى. حيث أظهرت النتائج انخفاض مقاومة البيتون على الضغط  والشد الفلق والانعطاف وانخفاض الوزن الحجمي أيضاً وذلك بزيادة نسبة استبدال الحصويات الطبيعية بحصويات بيتونية معاد تدويرها.